Is MG53 a potential therapeutic target for cancer? - Du, Yunyu; Li, Tieying; Yi, Muqing (Frontiers in Endocrinology, 2023)
Cancer treatment still encounters challenges, such as side effects and drug resistance. The tripartite-motif (TRIM) protein family is widely involved in regulation of the occurrence, development, and drug resistance of tumors. MG53, a member of the TRIM protein family, shows strong potential in cancer therapy, primarily due to its E3 ubiquitin ligase properties. The classic membrane repair function and anti-inflammatory capacity of MG53 may also be beneficial for cancer prevention and treatment. However, MG53 appears to be a key regulatory factor in impaired glucose metabolism and a negative regulatory mechanism in muscle regeneration that may have a negative effect on cancer treatment. Developing MG53 mutants that balance the pros and cons may be the key to solving the problem. This article aims to summarize the role and mechanism of MG53 in the occurrence, progression, and invasion of cancer, focusing on the potential impact of the biological function of MG53 on cancer therapy.